Resilient Distributed Multiagent Control for AC Microgrid Networks Subject to Disturbances - Lai, Jingang; Lu, Xiaoqing; Dong, Zhaoyang; Cheng, Shijie (IEEE transactions on systems, man, and cybernetics. Systems, 2022)
In actual microgrids (MGs) networks, the information exchange between distributed energy resources (DERs) agents may be subject to various types of measurement noises and effected by communication time delays. This article proposes a resilient distributed multiagent control scheme for ac MG networks subject to additive noise and time-delay disturbances. The proposed multiagent control scheme is composed of three distributed consensus protocols, which is able to synchronize the output voltages and frequencies of inverter-based DERs to their reference values and achieve the optimal active power-sharing property by a low bandwidth communication network with noise and time-delay disturbances in almost sure convergence. By means of the stochastic analysis tools and algebraic graph theory, distributed consensus control protocols are designed to be employed for the secondary control level of MGs. On this basis, we deduce the stability criteria of the closed-loop MG system under noise and time-delay disturbances. As a result, the proposed consensus protocols can well restore the voltage and frequency's derivation produced at the primary control level, meanwhile, can well achieve the optimal power sharing even though there exist communication disturbances. Several simulation scenarios on an islanded MG network are provided to verify the proposed control protocols' performance.